Zur Gestalt des Meeresbodens im nordatlantischen Ozean - Ulrich, Johannes (ERDKUNDE, 1963)
The paper evaluates the echograms of the research ships F.F.S. Anton Dohrn and V.F.S. Gauss as regards their geomorphological contents. The sounding profiles, whose position is given in fig. 1, are longitudinal and transversal profiles of the major and numerous minor relief features of the sea bed. The N.W.-S.E. profiles from the area of the Irming Sea represent the S.E. shelf of Green land, as well as the island's slope and foot regions, the north-eastern Labrador Basin and Reykjanes Ridge (fig. 2). The Mid-Atlantic Ridge between 50°N and 57°N shows in its west regions (zone of block fractures, horst-graben zone with central rift) a particularly complicated relief. The central rift valley can be followed clearly even across the zone where the ridge changes its direction (fig. 3 and 5). The rise from the southern Iceland Basin to the Rockall Plateau, the broad plateau itself, and the southern part of the Rockall Bank appear in contrast as pronounced major features with little variations within. At the foot of the Rockall Bank on the approximately 1,400 m. deep plateau a deepening of about 200 m. was recognised, which is interpreted as a deep sea furrow (fig. 4). Mainly balanced forms are also revealed by the sounding profiles across the Newfoundland shelf, the steep section and foot region of the North American continental slope as well as across the Newfoundland deep sea plain, which is bisected by the already known Mid-Ocean Canyon (fig. 6 and 7). Between the deep sea plain and the hill region of the deep sea in the Newfoundland Basin a region of rounded elevations - Gauss Kuppen - was discovered within 44°N/45°N and 39°W/41°30’W, whose highest summits rise from over 4,500 m. to about 2,000 m. below sea level. A further region of rounded elevations within the legendary Milne Bank was surveyed by V.F.S. Gauss and is here represented by a number of sounding profiles and also in the form of an isobath map. Particularly interesting morphological results ensued from the survey of the Anton Dohrn Kuppe, situated in the Rockall channel between Rockall and St. Kilda, which was discovered by V.F.S. Gauss on the return trip from its I.G.Y. voyages, and later visited several times by F.F.S. Anton Dohrn (fig. 9). In a com prehensive map of the morphological regions the results of the soundings of both research ships have been coordinated with the findings of American marine geologists (B. C. Heezen and others, 1959) (fig. 10).